RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA BAYU BERBASIS TURBIN VERTIKAL SEBAGAI ALAT PENGUKURAN TEGANGAN KELUARAN - Kevin Nuansa Aghita Sembiring; Usman Usman; Fauziah Nur (Smart Education, 2025)
Abstract: This final project discusses the design and construction of a Vertical Axis Wind Turbine (VAWT)-based Wind Power Plant (PLTB) as a prototype for measuring output voltage. The system employs a Darius-type vertical wind turbine connected to a BLDC (Brushless Direct Current) motor functioning as a generator. The generator produces three-phase AC voltage, which is then rectified using a three-phase full-wave bridge rectifier with six diodes to generate DC voltage. The research focuses on testing the relationship between wind speed and output voltage on both the AC and DC sides. Measurements were carried out using a digital multimeter with artificial and natural wind sources. The results show that the output voltage increases with higher wind speed, and after rectification, the generated DC voltage is relatively stable and consistent with the theory of electrical energy conversion. Overall, the PLTB prototype successfully operates as intended to generate electrical voltage from wind energy and can serve as a reference for analyzing the performance of small-scale wind power systems as well as the development of renewable energy technologies. Keywords: Wind Power Generator, Vertical Axis Wind Turbine, Renewable Energy. Abstrak: Proyek akhir ini membahas Rancang Bangun Pembangkit Listrik Tenaga Bayu (PLTB) Berbasis Turbin Vertikal sebagai prototipe alat pengukuran tegangan keluaran. Sistem menggunakan turbin angin vertikal tipe Darius yang dihubungkan dengan motor BLDC (Brushless Direct Current) sebagai generator. Tegangan AC tiga fasa yang dihasilkan kemudian disearahkan melalui rangkaian three-phase full-wave bridge rectifier dengan enam dioda untuk menghasilkan tegangan DC. Penelitian difokuskan pada pengujian hubungan kecepatan angin dengan tegangan keluaran pada sisi AC maupun DC. Pengukuran dilakukan menggunakan multimeter digital dengan sumber angin buatan maupun alami. Hasil menunjukkan bahwa tegangan keluaran meningkat seiring bertambahnya kecepatan angin, dan setelah penyearahan menghasilkan tegangan DC yang stabil sesuai teori konversi energi listrik. Secara keseluruhan, prototipe PLTB ini berhasil berfungsi sesuai tujuan untuk menghasilkan tegangan listrik dari energi angin, serta dapat dijadikan acuan analisis kinerja sistem PLTB skala kecil dan pengembangan energi terbarukan. Kata kunci: : Pembangkit Listrik Tenaga Bayu,Turbin Angin, Energi Terbarukan.